If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3ln(x) + -1ln(3x) = 0 Multiply ln * x 3lnx + -1ln(3x) = 0 Remove parenthesis around (3x) 3lnx + -1ln * 3x = 0 Reorder the terms for easier multiplication: 3lnx + -1 * 3ln * x = 0 Multiply -1 * 3 3lnx + -3ln * x = 0 Multiply ln * x 3lnx + -3lnx = 0 Combine like terms: 3lnx + -3lnx = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| y=1.8x+4 | | 74-2x=-46+6x | | 18u-9u=19 | | y=700+60y | | 18+4y=-5y | | 7-2=z+2-2 | | -39-12x=-7x+26 | | 4(1.5+6)-2=-9 | | m(m+6)=72 | | 73+4x=-5x-134 | | y=390+60y | | 4x^2-16x=-15 | | 72+4x=-5x-134 | | 2(w^2)-9w=0 | | y=510+60y | | -40+-6= | | 5x-34=-2x+78 | | 21x-400=x | | 112=-41+9x | | 12(3x-4)=3(12x+6) | | y=590+.60y | | 2X-1=33+X | | 10-3x=58 | | 5*0-4y=-20 | | 4x-58=-x+27 | | 6+12m-2=7m+76-3m | | -80=-5x-30 | | -6x-10=32 | | x^4+10x^3+36x^2+56x+32=0 | | -2p+8=5-(9p+6) | | -12x=288 | | m(7+m)=78 |